Tinjauan Yuridis Terhadap Daftar Pemilih Dalam Penyelenggaraan Pemilihan Umum Legislatif Berdasarkan Peraturan Komisi Pemilihan Umum Nomor 9 Tahun 2013 Tentang Penyusunan Daftar Pemilih Untuk Pemilihan Umum Anggota Legislatif - Oktavia, Ika Fransiska; Firdaus, Emilda; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Judicial Review of the Voters List in the implementation of the legislative elections based on the Regulation of the General Election Commission Number 9 of 2013 on the Compilation of the General Election List of Legislative Members has clearly stated that the process of updating the voters list from the Temporary Voter List (TVL), Temporary Voter List Result of Improvement (TVLRI), Permanent Voter List (PVL), Supplementary Voter List (SPVL) and Special Voters List (SVL) have been neatly arranged through synchronization or matching of population data conducted by the Minister of Home Affairs to the General Election Commission (GEC). The main problem in this research is how the process of compiling the voter list and the efforts that can be done by the General Election Commission (GEC) of Riau Province as the organizer of the General Election.This type of research uses sociological legal research method, which is a legal research that wants to see the correlation between law and society so that it can know the enactment of positive law within the society or review the existing problems in the field related to the applicable legal aspects and which regulate the problem.The result of this research is that the failure of the realization of the implementation of program / activity of stages pemutkhiran data of Voters and the compilation of voter list by General Election Commission (GEC) Riau Province and ranks, General Election Commission (GEC) of Riau Province and its staffs do not want to involve Election Supervisory on supervision preliminary data requirements, Aggregate Data of Population (ADP) and matching by the General Elections Commission (GEC) of Riau Province, in addition to the participation of the General Election is less concerned with the prevailing laws and regulations in publicizing and socializing regulations related to the determination of the voters list as a precautionary measure of the violation of the General Election.Keywords: Updates-List of Voters-General Election.